Situational and Dispositional Factors in Rape Cognitions: The Roles of Social Media and the Dark Triad Traits - Lyons, Minna (Journal of interpersonal violence, 2022)
Previous research has established the importance of socially aversive personality traits (i.e., the Dark Triad) in rape cognitions (operationalized here as rape-supportive attitudes, rape victim empathy, and hostile masculinity). However, less is known about how sexist social media content influences attitudes toward rape cognitions depending on the personality of the individual. In an online experiment, after completing the Short Dark Triad-3 questionnaire, participants (N = 180) were primed with either sexist or neutral tweets, rating them for acceptability, humor, rudeness, and ignorance. Participants then completed scales for rape-supportive attitudes, victim empathy, and hostile masculinity. Sexist tweets were rated as significantly less acceptable and humorous, and more rude and ignorant than neutral tweets. However, those high in the Dark Triad found the sexist tweets as funny and acceptable. Overall, exposure to the sexist tweets did not increase rape cognitions. Moreover, the Dark Triad traits had similar significant, positive correlations with rape-supportive attitudes, victim blame, and hostile masculinity in both sexist and neutral tweet conditions. Multiple regression analyses (controlling for gender) revealed that psychopathy was the strongest positive predictor for increased rape cognitions. Findings suggest that short exposure to sexist social media content may not influence rape cognitions, but that dispositional factors such as psychopathy are more important.